2014
DOI: 10.1111/tmi.12369
|View full text |Cite
|
Sign up to set email alerts
|

Understanding factors, outcomes and reasons for loss to follow‐up among women in Option B+ PMTCT programme in Lilongwe, Malawi

Abstract: Abstractobjective To assess factors, outcomes and reasons for loss to follow-up (LTFU) among pregnant and breastfeeding women initiated on a lifelong antiretroviral therapy (ART) for PMTCT in a large antenatal clinic in Malawi.methods We identified all pregnant and breastfeeding women who were initiated on ART between September 2011 and September 2013 and had missed their clinic appointment by at least 3 weeks at Bwaila Hospital, the largest antenatal clinic in Malawi. These women were traced by phone or home … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

19
178
9

Year Published

2015
2015
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 164 publications
(206 citation statements)
references
References 18 publications
19
178
9
Order By: Relevance
“…This may be because individuals with low or no formal education are less likely to understand the information provided about their illness and treatment course in English. One study on outcomes and reasons for LTFU among HIV-infected women reported that inability to understand the information provided was a reason for LTFU [79]. This finding suggests that providing educational materials in local languages may contribute to improved retention.…”
Section: Discussionmentioning
confidence: 99%
“…This may be because individuals with low or no formal education are less likely to understand the information provided about their illness and treatment course in English. One study on outcomes and reasons for LTFU among HIV-infected women reported that inability to understand the information provided was a reason for LTFU [79]. This finding suggests that providing educational materials in local languages may contribute to improved retention.…”
Section: Discussionmentioning
confidence: 99%
“…Their inclusion in the study cohort might have increased overall short-term losses to care as reported elsewhere. 30,31 Lastly, despite basic interventions to ensure fidelity, no specific data were collected to report on fidelity to the piloted model. The present study highlights useful directions for future research.…”
Section: Discussionmentioning
confidence: 99%
“…15 A sizable proportion of women – who may feel healthy – refuse or default from cART 4,16,17 or receive no ARVs at all, 18 putting them at risk of increased MTCT. Data on long-term retention and adherence are as yet lacking.…”
Section: Introductionmentioning
confidence: 99%